PROPOSED ALTERNATIVE STRATEGY OF CARRIABLE PACKAGE COFFEE BUSINESS (CASE: CICIPI KOPI) (The Indonesian Journal of Business Administration, 2019)
Coffee is one of the most popular drinks in the world. Coffee is also popular in Indonesia. In 2016, coffee shops in Indonesia began to develop, especially in big cities. Cicipi Kopi is one business that runs in the field of coffee, precisely coffee drinks. Coffee sold has good taste and quality, and is valued at reasonable prices for the quality and taste that it gets. The problem faced by Cicipi Kopi is the reduction in sales from time to time. Research will focus on finding solutions that can help Cicipi Kopi. Research uses qualitative methods. In this study, internal and external analysis will be carried out to help find the right solution to solve the problem from Cicipi Kopi and increase sales.Keywords: Coffee, Indonesia coffee, internal and external analysis